Chemoselective Chromium(II)‐Catalyzed Cross‐Coupling Reactions of Dichlorinated Heteroaromatics with Functionalized Aryl Grignard Reagents. Issue 5 (2nd December 2014) - Steib, Andreas K.; Kuzmina, Olesya M.; Fernandez, Sarah; Malhotra, Sushant; Knochel, Paul
Abstract Chromium(II) chloride catalyzes the chemoselective cross‐coupling reaction of dichloropyridines with a range of functionalized (hetero)aromatic Grignard reagents at room temperature. Functional groups, such as esters and acetals, are well tolerated in this transformation. Previously challenging substrates, quinolines and isoquinolines, participate in the selective Cr‐catalyzed cross‐coupling in cyclopentyl methyl ether (CPME) as the solvent. The effective purging of Cr salts is demonstrated by using various solid supports.